Idiosyncratic volatility puzzle: influence of macro-finance factors - Aslanidis, Nektarios; Christiansen, Charlotte; Lambertides, Neophytos; Savva, Christos S. (My University, 2019)
We analyze the cross-sectional relation between expected idiosyncratic volatility and stock returns. The expected idiosyncratic volatility is conditioned on macro-finance factors as well as traditional asset pricing factors. The macro-finance factors are constructed from a large set of macroeconomic and financial variables. Our results show that the negative relation between expected idiosyncratic volatility and stock returns reverses to a positive one when accounting for the macro-finance effects. Portfolio analysis shows that the positive relation is economically important. The relation between expected idiosyncratic volatility and returns is not affected by business cycle variations. The empirical results are highly robust.
Keywords: Business cycle; Idiosyncratic volatility puzzle; Macro-finance factors